PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS TERHADAP SEMANGAT KERJA PEGAWAI MEDIS (Studi Kasus RSUD Salak Kab. Pakpak Bharat) - Riris E.H Naiborhu; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Democratic style of leadership is the ability to influence others to want work together to achieve purpose set by way of various activities to be carried out jointly determined between leaders and subordinates. Leaders established it self as a controller, regulatory and supervisory from such organizations do not impede the rights of subordinates to argue. Spirit work is the willingness of each individual or group to cooperate with enterprising, discipline, and sense of responsibility in carrying out its intended purpose.The research was conducted at RSUD Salak Kab. Pakpak Bharat is located in Jalan Raja David, Kec. Salak Kab.Pakpak Bharat. The purpose of this research was conducted to determine the effect democratic style of leadership about spirit work medical staff at RSUD Salak Kab. Pakpak Bharat.The method used in this research was descriptive and quantitative with SPSS program, Where the sampleused is all medical staff RSUD Salak Kab. Pakpak Bharat in 2014, and as a source of informationis the HRD, SIE data, information and medical records. To determine the sample using census method. The technique of collecting data through interviews, observation and questionnaires.The results of data analysis includestest validity, reliability, andsimple linear regression, Democratic styleof leadership in this research include the involvement of employeesin decision-making, superior and subordinate relationships. Each one has an indicator interrelated and influence positively about spirit work medical staff in RSUD Salak Kab. Pakpak Bharat. The results of this research concluded, t value (6,224) > t tabel (1,990) and Sig. (0,000) < 0,05.This means that the democratic style of leadership variable significant effect of spirit work.Keyword : democratic style ofleadership , spirit work